ANALISIS USAHA PENGOLAHAN IKAN TENGGIRI (Scomberomorus commerson) ASIN KERING DI DESA MUARA KINTAP KECAMATAN KINTAP KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Maria Ulfah Riani; Emmy Sri Mahreda; Rina Mustika Mustika (Fish Scientiae, 2019)
Muara Kintap village in Kintap District Kabupaten Tanah Laut is a centralarea of salted dried mackerel processing and becoming famous in South Kalimantan. The salted dried mackerel fish produced in Muara Kintap village is better quality compared with the mackerel fish produced in another villages distributed in South Kalimantan. The mackerel fish is directly handled by salted anddried on vessel after caught on sea. This purposes from research are to know benefit,feasibility, sensitivity fluctuation price, variation price, and marketing chanell frombusiness analysis of salted dried mackerel while research method used is census.Salted dried mackerel fish processing is becoming an advantagous business in the Muara Kintap village becaused total revenue is greater than total cost, and wellabove the BEP during and in out of the fishing seasons. Based on the analysis of thefeasibility of the NPV at 13% = 82.088.266 Net BCR 13% = 1,148, and IRR =15,3%, the salted dried mackerel fish processing business is worth to the effort.Likewise when not in season the NPV 13% = 132.237.410, Net BCR 13% =1,277, and IRR = 16,7%. It can be said that the salted dried mackerel fish business is more feasible in out of the season. The results of sensitivity analysis with an increase of 25% diesel and 50% salt for processing is sensitive to the time of the season while at no season is not sensitive to the increase in input prices. The average saleprice fluctuation of salted dried mackerel fish in the village Muara Kintap between atthe season and when out of the season of 48,09%, and variation price the season Rp42.000,00 – Rp 48.000,00 while at no season Rp 64.000,00 – Rp 68.000,00. There are two marketing channels of salted dried mackerel fish in the Muara Kintap inclouding:- Fishermen Collecting - Fishermen-Collecting-Consumen